NAM—help or burden? Intercultural evaluation of parental stress caused by nasoalveolar molding: a retrospective multi-center study - Roth, Maximilian; Lonic, Daniel; Grill, Florian D.; Ritschl, Lucas M.; Loeffelbein, Denys J.; Wolff, Klaus Dietrich; Niu, Lien Shin; Pai, Betty Chien Jung; Prantl, Lukas; Kehrer, Andreas; Heidekrüger, Paul I.; Rau, Andrea; et al. (Clinical Oral Investigations, 2021)
Objectives: Nasoalveolar molding (NAM) was developed to facilitate easier treatment and better outcomes for cleft lip and palate (CLP) patients. The aim of this study was to investigate the parental burden and possible intercultural differences of this treatment modality, which is often argued to burden parents to an extraordinary amount. Materials and methods: Standardized questionnaires (available in English, Mandarin, and German) with 15 non-specific and 14 NAM-specific items to be retrospectively answered by Likert scales by parents of unilateral CLP patients with completed NAM treatment. Results: The parents of 117 patients from two treatment centers in Taiwan and Germany were included. A very high level of overall satisfaction was found in both countries with significant intercultural differences in prenatal parent information, feeding problems, dealing with 3rd party’s perception, and experienced personal effort. Conclusion: NAM is an effective treatment tool for children’s CLP deformities and their caregivers in overcoming the feeling of helplessness. Intercultural differences may be due to infrastructural reasons, cultural attitudes and habits, or different public medical education. Clinical relevance: In addition to facilitating easier surgical treatment, NAM can be seen as a powerful coping strategy for parents dealing with a CLP deformity of their child and does not seem to burden them extraordinarily.
CRIS-Team Scopus Importer:2021-03-19
Keywords: Burden; Cleft lip palate; Intercultural evaluation; Nasoalveolar molding; Parental stress; Questionnaire